Maqasid al-syariah & human well-being: a study on Melaka's public housing - Shuid, Syafiee; Mohd Zamin, Muhammad Faid (Malaysian Institute Of Planners, 2018)
The need for proper housing for the people is an undeniable necessity that should be constantly monitored and researched. Housing opportunities should be made available for every individual, regardless of their income as it can be considered as one of the basic necessities for human life. In Islam, it preaches on a just, ethical, non-discriminatory (Qayyim, 1347 C.E.) and efficient protection of its follower's well-being, especially in providing social necessities such as housing. The relationship between the function of Maqasid al-Syariah and the public housing would be examined in this paper to determine the effectiveness of the Maqasid al-Syariah in the protection of human well-being. In order to analyze the relationship, a set of questionnaires pertaining on the satisfaction level of the society towards the housing market is distributed to 400 respondents equally divided among the three districts in Melaka. The study also concerns itself with the public housing community, as the focus of this research is aimed at the bottom 40% social group in Melaka. Under the Maqasid al-Syariah, the three domains which are the darurriyat (needs), hajiyyat (necessities), and tahsiniyyat (luxuries) are analysed based on the homeownership, housing condition, financial capacity and physical environment. © 2018 by MIP.